Active Thermoplastic Starch Film with Watermelon Rind Extract for Future Biodegradable Food Packaging - Tatsaporn Todhanakasem; Chayanit Jaiprayat; Thunchanok Sroysuwan; Supakanya Suksermsakul; Rachit Suwapanich; Kamolnate Kitsawad Maleenont; Piyawit Koombhongse; Briana M. Young (My University, 2022)
Petrochemical plastic wastes generate serious environmental problems because they are resistant to natural decomposition. The aim of this study was to develop a biodegradable active thermoplastic film composed of polyvinyl alcohol (PVA), corn starch (ST), glycerol, and the active compounds from watermelon rind extract (WMRE), or PVA/ST/WMRE, using the casting technique. The film was examined for its mechanical, antioxidant, and functional properties against selected foodborne pathogens. The results showed that the addition of 10% v/v of watermelon rind extract to the film formulation significantly increased the tensile strength from 19.44 ± 0.84 MPa to 33.67 ± 4.38 MPa and slightly increased the percent elongation at break (% EAB) from 35.04 ± 0.96% to 35.16 ± 1.08%. The antioxidant property of PVA/ST/WMRE film was analyzed based on the DPPH scavenging activity assay, which significantly increased from 29.21 ± 0.24% to 63.37 ± 4.27%. The minimum inhibitory concentration (MIC) of watermelon rind extract was analyzed for the growth inhibition of Bacillus cereus ATCC 11778, Escherichia coli ATCC 8739, and Salmonella enterica subsp. enterica serovar Typhimurium ATCC 13311, with 10% (v/v) found as an optimal concentration against B. cereus. Wrapping fresh-cut purple cabbage with PVA/ST/WMRE film significantly reduced the microbial load after 3 days of storage, in comparison to commercial packaging (PET) and thermoplastic control film. Consumer testing of the packaging film indicated that user acceptance of the product was favorable. Therefore, we suggest that this newly developed film can be used as a biodegradable food packaging item that will lead to enhanced food safety, food quality, prolonged shelf life, and consumer acceptance for further food applications.
Keywords: Bioplastic; Active packaging; Biodegradable polymer; Nanocomposite Films for Food Packaging